Isothiocyanates: a review - Chandra Kala*; Syed Salman Ali; Nabeel Ahmad; Sadaf Jamal Gilani; Najam Ali Khan (Iranian Society of Pharmacognosy, 2018)
Isothiocyanates (ITCs) are naturally occurring molecules belonging to highly reactive organosulphur synthons, with the general structure R-N=C=S. The precursor molecule glucosinolate anions are hydrolyzed enzymatically (under the effect of myrosinase enzymes) or unenzymatically to produce nitriles or isothiocyanates depending upon conditions such as pH and temperature. Brassicaceae  Family is known to contain abundant ITCs. A significant number of isothiocyanates has been isolated from different plant sources and some of them have been synthesized. Several isothiocyanates have demonstrated significant pharmacological activities including anti-cancer, anti-inflammatory, anti-microbial activities, etc. Pharmacokinetic profiles of these sulphur containing compounds are well established. However, safety profiles of ITCs need consideration and a well-designed study with appropriate control, for their production as lead compounds. This review summarises the chemistry, sources, pharmacokinetics, pharmacological activity and toxicity profiles of the isothiocyanates.